2011 IEEE World Haptics Conference 2011
DOI: 10.1109/whc.2011.5945523
|View full text |Cite
|
Sign up to set email alerts
|

Conveying intentions through haptics in human-computer collaboration

Abstract: Haptics has been used as a natural way for humans to communicate with computers in collaborative virtual environments. Humancomputer collaboration is typically achieved by sharing control of the task between a human and a computer operator. An important research challenge in the field addresses the need to realize intention recognition and response, which involves a decision making process between the partners. In an earlier study [11], we implemented a dynamic role exchange mechanism, which realizes decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The questionnaire consists of 20 questions taken from NASA-TLX task load index (Hart and Stavenland, 1988) as well as those developed by Kucukyilmaz et al (2011). The subjects indicate their level of agreement or disagreement on a 7-point Likert scale for a series of questions, some of which are rephrased and asked again within the questionnaire in an arbitrary order.…”
Section: Subjective Measuresmentioning
confidence: 99%
“…The questionnaire consists of 20 questions taken from NASA-TLX task load index (Hart and Stavenland, 1988) as well as those developed by Kucukyilmaz et al (2011). The subjects indicate their level of agreement or disagreement on a 7-point Likert scale for a series of questions, some of which are rephrased and asked again within the questionnaire in an arbitrary order.…”
Section: Subjective Measuresmentioning
confidence: 99%
“…Oguz et al [10] proposed a role exchange model for dynamic dyadic interaction between a computer and a human, where the computer offers haptic assistance based on the intent of the human partner. Later, Kucukyilmaz et al [11] further showed that explicitly displaying the role state to the partners improves the sense of collaboration and creates a stronger sense of trust toward the computer. Evrard and Kheddar [12] investigated human-robot haptic interaction and offered a model that allows the robot partner to switch between leader and follower roles during the execution of a task.…”
Section: Haptic Interactionmentioning
confidence: 99%
“…2) is similar to the one presented in our earlier work [10], [11]. The human control is supplied to the system through a PHANToM Omni device, which is used to control the Haptic Interface Point (HIP) in our physics-based model.…”
Section: The Physics-based Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we extend the work presented in [5] to further evaluate the benefits and the usability of a RE mechanism as a shared control scheme. As a testbed, we used a target-hitting task, and developed a model for haptic collaboration in which the human and the computer interact through force to achieve a common goal by dynamically exchanging roles.…”
Section: Introductionmentioning
confidence: 95%